Pseudopyronine B: a potent antimicrobial and anticancer molecule isolated from a Pseudomonas mosselii strain - KUMAR, NISHANTH S.; SR, Aravind; JACOB, JUBI; Gopinath, Gethu; Lekha, Sree; Kumar BS, Dileep; L, Ravi shanker (Frontiers in Microbiology, 2017)
In continuation of our search for new bioactive compounds from soil microbes, a fluorescent Pseudomonas strain isolated from paddy field soil of Kuttanad, Kerala, India was screened for the production of bioactive secondary metabolites. This strain was identified as Pseudomonas mosselii through 16S rDNA gene sequencing followed by BLAST analysis and the bioactive metabolites produced were purified by column chromatography (silica gel) and a pure bioactive secondary metabolite was isolated. This bioactive compound was identified as Pseudopyronine B by NMR and HR-ESI-MS. Pseudopyronine B recorded significant antimicrobial activity especially against Gram-positive bacteria and agriculturally important fungi. MTT assay was used for finding cell proliferation inhibition, and Pseudopyronine B recorded significant antitumor activity against non-small cell lung cancer cell (A549), and mouse melanoma cell (B16F10). The preliminary MTT assay results revealed that Pseudopyronine B recorded both dose- and time-dependent inhibition of the growth of test cancer cell lines. Pseudopyronine B induced apoptotic cell death in cancer cells as evidenced by Acridine orange/ethidium bromide and Hoechst staining, and this was further confirmed by flow cytometry analysis using Annexin V. Cell cycle analysis also supports apoptosis by inducing G2/M accumulation in both A549 and B16F10 cells. Pseudopyronine B treated cells recorded significant up-regulation of caspase 3 activity. Moreover, this compound recorded immunomodulatory activity by enhancing the proliferation of lymphocytes. The production of Pseudopyronine B by P. mosselii and its anticancer activity in A549 and B16F10 cell lines is reported here for the first time. The present study has a substantial influence on the information of Pseudopyronine B from P. mosselii as potential sources of novel drug molecule for the pharmaceutical companies, especially as potent antimicrobial and anticancer agent.